2015
DOI: 10.1371/journal.pone.0130536
|View full text |Cite
|
Sign up to set email alerts
|

Higher Serum Angiotensinogen Is an Indicator of IgA Vasculitis with Nephritis Revealed by Comparative Proteomes Analysis

Abstract: IgA vasculitis (IgAV), previously named as Henoch–Schönlein purpura, is the most common systematic vasculitis with unknown etiology. Lack of appropriate study system and/or animal model limits the understanding of its molecular pathogenesis and hinders the identification of targets for rational therapy, especially for its long-term complication, IgAV nephritis (IgAVN). In this study, we applied comparative analysis of serum proteomes to obtain an insight about disease pathogenesis. This study has utilized high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Previously, He et al have reported that the Wnt signaling pathway may be involved in the modulation of HSPN pathogenesis [10]. In this study, this pathway was found to be active during the progression of HSPN from type 2 to type 3 ( Supplementary Table S5), a period when renal injury can be relatively serious.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…Previously, He et al have reported that the Wnt signaling pathway may be involved in the modulation of HSPN pathogenesis [10]. In this study, this pathway was found to be active during the progression of HSPN from type 2 to type 3 ( Supplementary Table S5), a period when renal injury can be relatively serious.…”
supporting
confidence: 58%
“…Recently, there have been several HSP-related researches using genome-wide methods, including a thorough review published in Autoimmunity Reviews summarizing the genetic component associated with the pathogenesis of HSP [9]. Researchers in China have reported on the proteomic alterations between HSP and HSPN patients in the Chinese population using comparative proteomic analysis [10]. Additionally, we previously published a study that revealed three potential biomarkers associated with the progression of HSP to HSPN [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, proteomic analysis of HSPN has rarely been studied, especially in urine. He XL et al performed a comparative analysis of serum proteomes by LC-MS/MS that revealed proteomic alterations in HSPN patients [19]. An analysis of urinary polypeptides from HSPN patients by electrophoretic methods detected urine proteins such as collagen alpha-1 (I) and (III) and alpha-1-antitrypsin [20].…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin A vasculitis (IgAV), formerly Henoch–Schönlein purpura (HSP), is a type of systemic small vessel vasculitis characterised by transmural vessel wall inflammation with leukocyte disintegration accompanied and probably triggered by IgA depositions . Respiratory infections are considered a key trigger for the generation and deposition of IgA immune complexes with increased IgAV frequency reported during colder months .…”
Section: Introductionmentioning
confidence: 99%